Geochemical proxy of sediment cores from Terengganu coastal water, Malaysia - Yunus, Kamaruzzaman; Shaari, Hasrizal; Ong, Meng Chuan; Khan Chowdhury, Ahmed Jalal; Saad, Shahbudin; B.I, Mohd Nizam (Oriental Scientific Publishing Co., 2009)
Two 40 cm sediment cores were sampled at the Terengganu coastal water within TR1 and TR2. The concentration of heavy metals (Co, Cu and Pb) was analyzed using the Inductively Coupled Plasma Mass Spectrometry (ICPMS). The average concentration of Co in core TR1 and TR2 were of 11.2 ± 1.03 μg/g dry weights and 8.38 ± 2.08 μg/g dry weights, and the average concentration of Cu were of 11.3 ± 0.88 μg/g dry weights and 8.06 ± 2.14 μg/g dry weights, respectively. The average concentration of Pb in TR1 and TR2 were 30.48 ± 6.91 μg/g dry weight and 18.85 ± 5.57 μg/g dry weights, respectively. The calculated enrichment factor (EF) values for the metals were closeto 1 and may therefore be considered to be predominantly terrigenous in origin.